Formasi dan Negosiasi Ideologi dalam Novel Entrok Karya Okky Madasari: Analisis Hegemoni Gramscian - Radevi Oktaviani (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2022)
This article aims to examine the ideological formations and negotiation in the novel Entrok by Okky Madasari. Data analysis used descriptive analysis method, namely describing the facts followed by analyzing them with a sociological approach to Gramsci's theory of hegemony. The ideologies that are analyzed to find the dominant ideology through the existing ideological formations. The data analysis technique uses content analysis techniques in the form of literary texts. The results of this study indicate that there are five dominant ideologies in this novel, namely 1.) conservatism, 2.) theism, 3.) pantheism, 4.) militarism, and 5.) bapakism. The five ideologies have correlation, subordination, and contradiction. Hegemony can be achieved through negotiations that occur in dialogue between characters. The novel Entrok has the ideology of conservatism as the most dominating ideology.